Unsafe Actions for Occupational Accidents in Construction Workers: A Systematic Literature Review - Mulia Fadhilatul Azizah; Novrikasari Novrikasari; Mohammad Zulkarnain; Pitri Noviadi (International Journal of Multidisciplinary Sciences and Arts, 2025)
The sector with a high accident rate in Indonesia is the trade and services sector (21.4%), which in this case includes construction. 32% of work accident cases that occurred in Indonesia throughout 2017 were work accidents in the construction sector. It is stated that 88% of work accidents occur due to unsafe actions so it is necessary to conduct research regarding factors related to unsafe actions on work accidents in construction workers. This research uses Systematic Review and PRISMA. The data was obtained from related research that has been collected by the author. A total of 8 journals were used in this research. Knowledge, use of PPE, and supervision are related to unsafe actions towards work accidents in construction workers. It is necessary to provide training and education to increase workers' insight into Occupational Health and Safety knowledge, procedures for using tools and PPE so that workers are able to map the dangers and risks in their work and work environment. It is necessary to create rules/policies and a commitment from supervisors and management to take firm action against workers who violate rules such as not using PPE in the form of punishment.